VALUE OF INNOVATION BASIS ON SHARIAH - MANSUR CHADI MURSID (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of this paper is to analyze value of innovation as the role mediating in the relationship between NPD Innovation and NPD Performance, and also to clarified in Exploratory Factor Analysis and Confirmatory Factor Analysis. We proposed value of innovation basis on shariah as mediating role in this study developed from diffusion of innovations theory. The questionnaires will be given to only the managers of the board of shariah micro finance in Pekalongan and Banyumas, Indonesia with total 171 responden from 27 LKMS (Baitul Maal wa Tamwil, Baitul Tamwil, Kospin Jasa Shariah, and KSPP Shariah). Value of innovation basis on shariah significantly affect to marketing performance. Research limited in first order, future research can examined in second order research. LKMS adapted value of innovation basis on shariah to get product launch easily. Value of innovation basis on shariah as the new variable and theory concept. Indirect, NPD Innovation positive significantly affect to marketing performance with value of innovation basis on shariah and product launch success are as mediating role.